2021
DOI: 10.3892/ol.2021.12883
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assessment of the efficiency of the PIM‑1 kinase pharmacological inhibitor as a potential treatment for Burkitt's lymphoma

Abstract: Burkitt's lymphoma is an aggressive form of lymphoma affecting B lymphocytes. It occurs endemically in Africa and sporadically in the rest of the world. Due to the high proliferation rate of this tumor, intensive multi-drug treatment is required; however, the risk of tumor syndrome lysis is high. Overexpression of the proto-oncogene proviral integration of the Moloney murine leukemia virus (PIM-1) kinase is associated with the development of hematological abnormalities, including Burkitt's lymphoma (BL). PIM-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…This is based on the observation that the expression of PIM1 kinase could not be detected in three AML cell lines examined (HL-60, NB4, and U937) (Supplementary Figure S7), consistent with previous reports [35,36]. Notably, one chronic myeloid leukaemia cell line, K-562, was included in some preliminary experiments of this study, considering its higher expression of PIM1 [37]. Consistently, the K-562 cell line showed overexpression of PIM1 (Supplementary Figure S7), but surprisingly it was not sensitive to the selective and potent PIM1 kinase inhibitor, AZD1208 (K i against PIM1 < 1 nM), and displayed comparatively high GI 50 value (~38 µM) (Supplementary Figure S8A).…”
Section: Discussionsupporting
confidence: 88%
“…This is based on the observation that the expression of PIM1 kinase could not be detected in three AML cell lines examined (HL-60, NB4, and U937) (Supplementary Figure S7), consistent with previous reports [35,36]. Notably, one chronic myeloid leukaemia cell line, K-562, was included in some preliminary experiments of this study, considering its higher expression of PIM1 [37]. Consistently, the K-562 cell line showed overexpression of PIM1 (Supplementary Figure S7), but surprisingly it was not sensitive to the selective and potent PIM1 kinase inhibitor, AZD1208 (K i against PIM1 < 1 nM), and displayed comparatively high GI 50 value (~38 µM) (Supplementary Figure S8A).…”
Section: Discussionsupporting
confidence: 88%
“…PIM1 can enhance the activity of Bcl-2 by phosphorylating B cell lymphoma-2 protein (Bcl-2), thus promoting the proliferation of tumor cells and further promoting the invasion and migration of tumors [ 7 ]. It was also found that PIM1 can also phosphorylate the pro-apoptotic protein Bad, inactivating it, preventing the apoptosis of tumor cells, and promoting the survival of the cells [ 8 ]. PIM2 is highly expressed in malignancies, such as lymphoma and multiple myeloma [ 9 ].…”
Section: Introductionmentioning
confidence: 99%